The Impact of Product Boycotts on Franchise Agreements - Abu Khurais, Doaa Abdul Salam; Qashout, Ahmed Ramadan; Gubran , Adel Ali (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
Since the outbreak of the war in Gaza on October 7, 2023, calls for boycotts have intensified, urging the boycott of American and European products that support the Zionist entity, considering it an effective economic weapon. These campaigns began with the boycott of branches of major companies through franchise agreements, which are contracts between two parties: the franchisor (the trademark owner) and the franchisee (the beneficiary of the trademark in exchange for a fee paid to the former). With the spread of the boycott campaign, franchisees have suffered economically, resulting in difficulties in fulfilling their contractual obligations. This research examines the legal implications of economic boycotts on the contractual obligations of the parties involved in franchise agreements, exploring the distinctions between force majeure and hardship and their effects. Ultimately, we conclude that economic boycotts can, at times, be considered force majeure and, at other times, hardship, depending on the specific circumstances faced by the franchisee.